Humic and Acetic Acids Have the Potential to Enhance Deterioration of Select Plastic Soil-Biodegradable Mulches in a Mediterranean Climate - Brenda Madrid; Huan Zhang; Carol A. Miles; Michael Kraft; Deirdre Griffin-LaHue; Lisa Wasko DeVetter (Agriculture, 2022)
The perceived variability of plastic soil-biodegradable mulch (BDM) degradation has generated concerns about its functionality and sustainability, especially in climates and regions where biodegradation may be limited. This study evaluated the effects of surface-applied products (compost tea, dairy-based compost, humic and acetic acids) on the surface deterioration and visible degradation of three plastic BDMs (BASF 0.6, Novamont 0.6, and Novamont 0.7) and one cellulose paper mulch (WeedGuard Plus) in a Mediterranean climate. Deterioration was monitored for 10 months, and degradation was evaluated 6- and 12 months following soil incorporation. Deterioration varied between the two years of the study; however, the average deterioration for WeedGuard Plus reached 100%, BASF 0.6 and Novamont 0.6 achieved ≥80%, while Novamont 0.7 reached ≥70%. Application of humic and acetic acids increased BASF 0.6 deterioration, but only humic acid increased Novamont 0.7 deterioration. Scanning electron microscopy of mulch surfaces demonstrated evidence of microbial colonization; however, the surface-applied products did not enhance microbial counts. In-soil degradation of BDMs was inconsistent, but faster degradation occurred overall for starch- and polybutylene adipate-co-terephthalate (PBAT)-based BDMs. Future studies should continue to explore on-farm strategies to enhance in-soil degradation to meet the production system’s goals.